Nejlepší světové čtení - Francis, Dick, 1920-2010; Deaver, Jeffery, 1950-; Sparks, Nicholas, 1965-; Nichol, John, 1963-; Moserová, Jaroslava, 1930-2006; Popel, Jiří, 1955-; Cukrová, Markéta, 1972-; Jindra, Miroslav, 1929- (Nejlepší světové čtení, 2001)
Edice zkrácených verzí nejlepších románů současných autorů.